Fabrication of a Customized Ball Abutment to Correct a Nonparallel Implant Abutment for a Mandibular Implant-Supported Removable Partial Prosthesis: A Case Report - Hossein Dasht; Mohammadreza Nakhaei; Nafiseh teimouri (Mashhad University of Medical Sciences, 2017)
Introduction: While using an implant-supported removable partial prosthesis, the implant abutments should be parallel to one another along the path of insertion. If the implants and their attachments are placed vertically on a similar occlusal plane, not only is the retention improved, the prosthesis will also be maintained for a longer period. Case Report: A 65-year-old male patient referred to the School of Dentistry in Mashhad, Iran with complaints of discomfort with the removable partial dentures for his lower mandible. Due to the lack of parallelism in the supporting implants, prefabricated ball abutment could not be used. As a result, a customized ball abutment was fabricated in order to correct the non-parallelism of the implants. Conclusion: Using UCLA abutments could be a cost-efficient approach for the correction of misaligned implant abutments in implant-supported overdentures.